2018
DOI: 10.3390/molecules23092329
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bioactive Chemical Markers in Zhi zhu xiang Improving Anxiety in Rat by Fingerprint-Efficacy Study

Abstract: Zhi zhu xiang (ZZX for short) is the root and rhizome of Valeriana jatamansi Jones, which is a Traditional Chinese Medicine (TCM) used to treat various mood disorders for more than 2000 years, especially anxiety. The aim of the present work was to identify the bioactive chemical markers in Zhi zhu xiang improving anxiety in rats by a fingerprint-efficacy study. More specifically, the chemical fingerprint of ZZX samples collected from 10 different regions was determined by High Performance Liquid Chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Although contents of five main ingredients in ZZX have been detected, we also found that 47 active ingredients from network pharmacology in the treatment of PTSD were mainly iridoids, flavonoids, and chlorogenic acids. Previous studies also revealed that valtrate, isochlorogenic acid A, and hesperetin play a role in anxiolytic action mediated by corticosterone levels ( Shi et al, 2014 ; Wang et al, 2018 ); here, we found that the hormone levels on the HPA axis are significantly increased in PTSD mice, which suggests that the HPA axis may also be important in PTSD. Importantly, acevaltrate has been shown to scavenge oxygen-free radicals, reduce oxidative stress, and play a neuroprotective role in the antioxidant activity mechanism ( Wang et al, 2017 ).…”
Section: Discussionsupporting
confidence: 77%
“…Although contents of five main ingredients in ZZX have been detected, we also found that 47 active ingredients from network pharmacology in the treatment of PTSD were mainly iridoids, flavonoids, and chlorogenic acids. Previous studies also revealed that valtrate, isochlorogenic acid A, and hesperetin play a role in anxiolytic action mediated by corticosterone levels ( Shi et al, 2014 ; Wang et al, 2018 ); here, we found that the hormone levels on the HPA axis are significantly increased in PTSD mice, which suggests that the HPA axis may also be important in PTSD. Importantly, acevaltrate has been shown to scavenge oxygen-free radicals, reduce oxidative stress, and play a neuroprotective role in the antioxidant activity mechanism ( Wang et al, 2017 ).…”
Section: Discussionsupporting
confidence: 77%
“…The anti-anxiety effect of its ethanol extract was studied on empty bottle-stimulated rats using the open field and the elevated plus-maze tests. Four bioactive compounds (hesperidin, isochlorogenic acid A, isochlorogenic acid B, and isochlorogenic acid C) were identified as the chemical markers for that effect [ 46 ]. There are some reports about the antidepressant effect of extracts and essential oils from this species [ 60 , 68 , 69 , 70 ].…”
Section: Effect On the Central Nervous Systemmentioning
confidence: 99%
“…The 'fingerprint-efficacy relationship' was studied by correlating HPLC fingerprints with in vitro and in vivo tests. Four chemical components, hesperidin, isochlorogenic acid A, isochlorogenic B and isochlorogenic C are regarded as multiple biological markers for this anti-anxiety effect [97].…”
Section: Fingerprint-efficacy Analysis In Tcmmentioning
confidence: 99%